The Development of a Bilingual Children’s Storybook Based on the Local Wisdom of Su’u Sawa’u Sia Sawale to Enhance Sanggar Language Literacy - Syarifuddin, Syarifuddin; Fauziah, Naila; Muhtadi, Rahmat Arif (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aimed to develop a bilingual children’s storybook (Sanggar–Indonesian) grounded in the local wisdom of Su’u Sawa’u Sia Sawale to enhance students’ basic literacy in the Sanggar language. The objectives were to examine the developmental process of the product using the R&D approach with the ADDIE model and to assess the feasibility and effectiveness of the resulting product in improving Sanggar language literacy among students. The product was trialed to 15 students at SDN 2 Piong, Sanggar District, Bima Regency, West Nusa Tenggara Province. Data collection employed questionnaires and pre–post tests. Validation was conducted by three experts: the material expert awarded a perfect score of 20/20 (100%), the media expert scored 18/20 (90%), and the third validator (a teacher and native speaker of Sanggar) gave 40/40 (100%), producing an average feasibility rate of 97% (Very High). During implementation, students’ Sanggar language literacy scores increased significantly from an average pretest score of 16.67 to a posttest average of 76.93, demonstrating that the developed product is both feasible and effective in improving students’ basic literacy in Sanggar language.